A New Class of Tunable Heterojunction by using Two Support Materials for the Synthesis of Supported Bimetallic Catalysts. Issue 2 (14th November 2014) - Liao, Fenglin; Lo, Ben Tsz; Sexton, Douglas; Qu, Jin; Ma, Chensheng; Chan, Rath Chau‐Ting; Lu, Qin; Che, Renchao; Kwok, Wai‐Ming; He, Heyong; Fairclough, Simon; Tsang, Shik Chi Edman
Abstract Finely dispersed Rh or Pd nanoparticles are decorated with a small quantity of Fe atoms, originating from the controlled reduction of two supports, the mixed oxides of ZnFe2O4–Fe2O3, to form supported RhFe or PdFe bimetallic nanoparticles without significant change in particle size. The selectivity of ethylene glycol hydrogenolysis can be manipulated by adjusting the compositions of the catalysts. This reveals the important underlying principle for rational design and synthesis of new supported bimetallic nanoparticles by using two mixed oxides with a tailored heterojunction that exerts tuning catalytic properties.